Perceived Stressors of Public Teacher Education Students - Shanker, Jayanthi; Hishan, Sanil S (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted to determine the personal, home-related and school-related profile and stressors of students in Brigade School in India. The relationship between the profile variables and extent of stressors of the respondents and the difference in the stressors of the respondents when grouped by profile variables was likewise determined. The descriptive-correlational research design was used to describe and interpret the profile variables, the relationship between the profile variables and the extent of stressors, and the difference in the stressors when grouped according to profile variables. Majority of the 2,295 respondents are 19 years old, single, female, and Roman Catholics. They reside within driving distance from the school. Their mothers are mostly 46 year-old high school graduate housekeepers, and their fathers are mostly 48 year-old high school graduate farmers. The family consists of four siblings with two married and three unmarried siblings. They are third year Bachelor of Secondary Education students of. Financial-related factors were perceived the most stressful and environmental- related factors were ranked the least. On the average, all factors are “moderately stressful” and show moderate correlation with the students’ fathers’ educational attainments. Moreover, the stressors have a slight correlation with their mother’s occupation, campus, year level, and field of specialization. Hence, the null hypotheses were rejected. In conclusion, the respondents were moderately stressed financially, and their stress is interrelated to their father’s educational attainment, mother’s occupation, the campus where they are enrolled, year level, and field of specialization.